A morphological and molecular study of Hydrodynastes gigas (Serpentes, Dipsadidae), a widespread species from South America - Carvalho, Priscila S. [UNESP]; Zaher, Hussam; Silva Jr, Nelson J. da; Santana, Diego J. (Peerj Inc, 2020)
Background. Studies with integrative approaches (based on different lines of evidence) are fundamental for understanding the diversity of organisms. Different data sources can improve the understanding of the taxonomy and evolution of snakes. We used this integrative approach to verify the taxonomic status of Hydrodynastes gigas (Dumeril, Bibron & Dumeril, 1854), given its wide distribution throughout South America, including the validity of the recently described Hydrodynastes melanogigas Franco, Fernandes & Bentim, 2007. Methods. We performed a phylogenetic analysis of Bayesian Inference with mtDNA 16S and Cytb, and nuDNA Cmos and NT3 concatenated (1,902 bp). In addition, we performed traditional morphometric analyses, meristic, hemipenis morphology and coloration pattern of H. gigas and H. melanogigas. Results. According to molecular and morphological characters, H. gigas is widely distributed throughout South America. We found no evidence to support that H. gigas and H. melanogigas species are distinct lineages, therefore, H. melanogigas is a junior synonym of H. gigas. Thus, the melanic pattern of H. melanogigas is the result of a polymorphism of H. gigas. Melanic populations of H. gigas can be found in the Tocantins-Araguaia basin.
Keywords: Biodiversity; Integrative taxonomy; Melanism; Neotropical region; Polymorphism; Squamata; Synonymization; Xenodontinae; Watersheds